2021
DOI: 10.2337/dc21-0740
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Occupational Consequences for Families of Children With Type 1 Diabetes: The Mothers Take the Burden

Abstract: OBJECTIVE To investigate the occupational and financial consequences for parents following the onset of type 1 diabetes in their child. RESEARCH DESIGN AND METHODS A questionnaire assessing occupational and financial situations before and in the first year after the onset of diabetes was distributed to all families with a child ≤14 years of age at diagnosis with a diabetes duration of at least 12 months in nine German pediatr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
2
12
0
1
Order By: Relevance
“…Examining the associations of burdens with demographic and clinical features revealed that mothers reported significantly higher burdens than fathers. This finding is comparable to the previous study reporting mothers are more likely than fathers to experience occupational strains due to the diagnosis of T1D in their child [ 21 ]. Our finding is also congruent with the report from a Norwegian population-based survey examining an age-comparable sample as in our study.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Examining the associations of burdens with demographic and clinical features revealed that mothers reported significantly higher burdens than fathers. This finding is comparable to the previous study reporting mothers are more likely than fathers to experience occupational strains due to the diagnosis of T1D in their child [ 21 ]. Our finding is also congruent with the report from a Norwegian population-based survey examining an age-comparable sample as in our study.…”
Section: Discussionsupporting
confidence: 88%
“…The caregiving responsibilities affect women more severely than men. As evidenced in a previous study, mothers have shown commendable sacrifice to accept additional responsibility by compromising their current and future financial and occupational situations [ 21 ]. Supporting these families will not only provide relief for these mothers but also reduce social inequality among members of our community.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations